School inputs and student performance in public elementary schools in Palawan a quantile regression analysis - Punongbayan, Jan Carlo B. ([Quezon City] School of Economics, University of the Philippines, 2009)
This study investigates the role of school resources in different measures of student performance in public elementary schools in the province of Palawan. We contend that it is not enough to identify which school resources matter the most, but that it would be more informative for policy purposes to identify which student types may benefit the most from the provision of a given school resource. We also find that class size and pupil-room ratio improvements, along with the provision of guidance counselors and science laboratories, may benefit low-performing school the most.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 218-219)
Keywords: Public schools -- Economic aspects -- Philippines -- Palawan; Academic achievement -- Economic aspects -- Philippines -- Palawan; Education -- Economic aspects -- Philippines -- Palawan